1979
DOI: 10.1128/aac.15.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Isolates of Serratia marcescens Transferring Ampicillin, Carbenicillin, and Gentamicin Resistance to Other Gram-Negative Bacteria Including Pseudomonas aeruginosa

Abstract: Thirteen independent isolates of Serratia marcescens associated with nosocomial urinary tract infections were obtained from the clinical microbiology laboratory at Hines Veterans Administration Hospital. The isolates were resistant to at least ampicillin, carbenicillin, gentamicin, and tobramycin. They could be divided into two groups on the basis of their antibiotypes. Group I (9 strains) showed resistance to 13 antibiotics, including 3 beta-lactams, 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Strains of Escherichia coli were maintained on Luria-Bertani medium (27), and other bacteria were kept on Nutrient Agar medium (Difco). The minimal medium used for E. coli (22) was supplemented when appropriate with 100 ,ug of thiamine per ml or 25 p,g of proline per ml. The minimal medium for Agrobacterium, Pseudomonas, and Rhizobium spp.…”
Section: Methodsmentioning
confidence: 99%
“…Strains of Escherichia coli were maintained on Luria-Bertani medium (27), and other bacteria were kept on Nutrient Agar medium (Difco). The minimal medium used for E. coli (22) was supplemented when appropriate with 100 ,ug of thiamine per ml or 25 p,g of proline per ml. The minimal medium for Agrobacterium, Pseudomonas, and Rhizobium spp.…”
Section: Methodsmentioning
confidence: 99%
“…The R plasmids were transferred by the conjugation method (16). Matings of the original cultures (donors) with the recipient cultures were made by mixing 0.1 ml of a midexponential phase culture of the donor with 0.45 ml of a similar culture of the recipient in a test tube containing 0.45 ml of fresh brain heart infusion broth (BHI, Difco Laboratories, Detroit, Michigan), and the tubes were incubated with gentle shaking at 37 C for 3 hr.…”
Section: Methodsmentioning
confidence: 99%
“…We also showed that pFMH1010 is conjugally transmissible from nosocomial Serratia marcescens isolates to the P. aeruginosa laboratory strain, PA038-1 (23,24). The resulting transconjugants gain resistance to carbenicillin, gentamicin, tobramycin, kanamycin, streptomycin, and sisomicin (23,24).…”
mentioning
confidence: 91%
“…The standard bacterial strains and plasmids used are shown in Table 1. Rifampinresistant (Rif) mutants of Escherichia coli 1231 and P. aeruginosa PA0227 were isolated as previously described (23).…”
Section: Methodsmentioning
confidence: 99%